Physicochemical and bacteriological screening of pathogenic microorganisms from aquarium water collected from katabon area in Dhaka city (Stamford Journal of Microbiology, 2021)
Globally, the ornamental fish business has a high demand for its popularity as well as for its profitability. However, microbial contamination, nutrient depletion and accumulation of organic materials are the major factors in an aquafarming system which can cause death of aquatic animal and causes financial losses. This study aimed to determine the physicochemical and microbiological quality of fish aquarium water. Water of different time interval after treatment (7 days, 20 days, 30 days, 60 days, 90 days) were taken from the different aquariums. A set of physicochemical parameters such as temperature, transparency, pH, conductivity, dissolved oxygen, total dissolved solids, alkalinity, total hardness, conductivity were found within the approved standard concentration for fish. The present study also reveals the microbiological status of the aquaculture water where the total viable count ranging from 2.20×104 to 4.20×104 cfu/ml. Escherichia coli, Staphylococcus spp., and Pseudomonas spp. were present in all samples. Antimicrobial susceptibility tests were also done to determine the antibiotic resistance pattern of microbes isolated from aquarium water.Stamford Journal of Microbiology, Vol.11 (1) 2021: 20-23